A risk-based approach for assessing the recycling potential of an alkaline waste material as road sub-base filler material. (January 2018) - Di Gianfilippo, Martina; Verginelli, Iason; Costa, Giulia; Spagnuolo, Riccardo; Gavasci, Renato; Lombardi, Francesco
Highlights: Risk-based approach to assess a recycling option for an alkaline waste material. Use of lab leaching test results for the assessment of contaminants release. Evaluation of the effects of weathering in terms of release and associated risks. Application of Monte Carlo analysis to evaluate the effects of scenario conditions. Estimated groundwater concentrations affected by the type of test used and weathering. Abstract: In this work we present an integrated risk-based approach that can be used to evaluate the recycling potential of an alkaline waste material such as incineration bottom ash (BA) as unbound material for road sub-base construction. This approach, which is aimed at assessing potential risks to the groundwater resource (in terms of drinking water quality) and human health associated to the leaching of contaminants from the BA, couples the results of leaching tests for the estimation of source concentrations with the fate and transport models usually adopted in risk assessment procedures. The effects of weathering and of the type of leaching test employed to evaluate eluate concentrations were assessed by carrying out different simulations using the results of laboratory leaching tests. Specifically, pH-dependence and column percolation leaching tests were performed on freshly collected and 1-year naturally weathered BA samples produced from a grate-fired incineration plant treating Refuse Derived Fuel (RDF). To evaluate a broad span of possible scenario conditions, a Monte Carlo analysis was performed running 5000 simulations, randomly varying the input parameters within the ranges expected in the field. In nearly all the simulated conditions, the concentrations of contaminants in the groundwater for the specific type of BA tested in this work were well below EU and WHO drinking water quality criteria. Nevertheless, some caution should be paid in the case of the establishment of acidic conditions in the field since in this case the concentration of some elements (i.e. Al, Pb and Zn) is expected to exceed threshold values. In terms of risks to human health, for the considered utilization scenario the probability of exceeding the acceptable reference dose for water ingestion was usually less than 1% (except for Cr and Pb for which the probability was lower than 3.5% and 7%, respectively).